Neural Networks for Classification and Image Generation of Aging in Genetic Syndromes - Duong, Dat; Hu, Ping; Tekendo-Ngongang, Cedrik; Hanchard, Suzanna E. Ledgister; Liu, Simon; Solomon, Benjamin D.; Waikel, Rebekah L. (Frontiers in Genetics, 2022)
Background In medical genetics, one application of neural networks is the diagnosis of genetic diseases based on images of patient faces. While these applications have been validated in the literature with primarily pediatric subjects, it is not known whether these applications can accurately diagnose patients across a lifespan. We aimed to extend previous works to determine whether age plays a factor in facial diagnosis, as well as to explore other factors that may contribute to the overall diagnostic accuracy. Methods To investigate this, we chose two relatively common conditions, Williams syndrome and 22q11.2 deletion syndrome. We built a neural network classifier trained on images of affected and unaffected individuals of different ages and compared classifier accuracy to clinical geneticists. We analyzed the results of saliency maps and the use of generative adversarial networks to boost accuracy. Results Our classifier outperformed clinical geneticists at recognizing face images of these two conditions within each of the age groups (the performance varied between the age groups): (1) under 2 years old, (2) 2-9 years old, (3) 10-19 years old, (4) 20-34 years old, and (5) ≥35 years old. The overall accuracy improvement by our classifier over the clinical geneticists was 15.5% and 22.7% for Williams syndrome and 22q11.2 deletion syndrome, respectively. Additionally, comparison of saliency maps revealed that key facial features learned by the neural network differed with respect to age. Finally, joint training real images with multiple different types of fake images created by a generative adversarial network showed up to 3.25% accuracy gain in classification accuracy. Conclusions The ability of clinical geneticists to diagnose these conditions is influenced by the age of the patient. Deep learning technologies like our classifier can more accurately identify patients across the lifespan based on facial features. Saliency maps of computer vision reveal syndromic facial feature attributes change with the age of the patient. Modest improvements in the classifier accuracy were observed when joint training with both real and fake images. Our findings highlight the need for a greater focus on age as a confounder in facial diagnosis.